Short Selling Announcements and Stock Price Reactions: Evidence from the Malaysian Stock Market - Chan, Kar Hoong (2010)
This study aims to examine stock price reactions on selected stocks listed on Kuala Lumpur Stock Exchange (KLSE) vis-à-vis the short selling announcements. On 28th August 1997, the regulator of Malaysia re-impose short selling restrictions, there are 50 stocks which are restricted at this time. Subsequently, the regulator made the further removal of short selling restrictions announcement on 22nd December 2006 which there are 70 stocks are being selected. Both events provide some implications to investors on the market reactions on the short selling announcement. It is argued that stock prices are biased upward if short selling restrictions are present. If short selling restrictions exist, investors will not be able to react on the negative information, thus, stock prices will bias upward. Conversely, it is claims that stock prices will bias downward if short selling activities are restricted. This is because short sales restrictions would reduce the speed of adjustment of stock prices towards negative information. In another words, removal of short selling restrictions will help to complete the market by permitting fuller prices discovery. In this study, event study methodology was utilized to analyze the stock price reactions. The results on 28th August 1997 showed that the market reacted negatively towards the announcement of the re-imposition of short selling restrictions. This indicates that the market viewed the announcement as negative news. The second event which is being examined is the announcement on the further removal of short selling restrictions on 22nd December 2006. The results showed that the stock prices reacted positively. This is the indication that the market viewed the announcement as positive news. Therefore, market completeness is coherent with the reactions of the market on this event. Overall, this study offers significant implications to investors. The results implied that the announcement on the removal of short selling activities is welcome by investors. The positive reactions on the announcement also indicates that there are more supply in the market hence it increases the liquidity of the stock market. Thus, the indications from the results in this study will enable investors to construct their investment strategies.